Thermoplastic elastomer
By using the combination of materials such as linear tri-embedded copolymers and efficient mixing technology in thermoplastic elastomers, the problem of insufficient tensile and impact strength of thermoplastic elastomers is solved, and the comprehensive performance and flame retardant effect of the material are significantly improved.
Patent Information
- Application Number
- CN202411564902.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-13
AI Technical Summary
The tensile and impact strength of thermoplastic elastomers is poor, and the filler dispersion is poor.
Using a combination of linear tri-embedded copolymer, thermoplastic polyurethane, polyolefin elastomer, compatibility agent, antioxidant, lubricant, light stabilizer, nano calcium carbonate, flame retardant and talc powder, through high-speed mixing and twin-screw extrusion Thermoplastic elastomer with enhanced tensile and impact strength was prepared.
The tensile and impact strength of the thermoplastic elastomer is improved, the flame retardant and rigidity of the material is enhanced, and the uniform dispersion and overall performance of the filler are improved.
Smart Images

Figure CN119119674A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, in particular to a thermoplastic elastomer. Background Art
[0002] Thermoplastic elastomer is a material with high elasticity, high strength, high resilience, and can be injection molded. It can be recycled to reduce costs. It can be secondary injection molded, coated and bonded with base materials such as PP, PE, PC, PS, ABS, etc., or molded alone. Because TPE has a soft touch, excellent colorability, weather resistance and fatigue resistance, as well as excellent processing performance, it can be recycled.
[0003] Currently, the dispersion of fillers in thermoplastic elastomers is poor, and the dispersion of fillers in thermoplastic elastomers cannot be effectively enhanced, and the tensile and impact strengths of thermoplastic elastomers are poor. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a thermoplastic elastomer, which solves the problem of poor tensile and impact strength of the thermoplastic elastomer.
[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a thermoplastic elastomer, comprising the following raw materials in parts by weight: 30 to 50 parts of a linear triblock copolymer, 20 to 30 parts of a thermoplastic polyurethane, 10 to 20 parts of a polyolefin elastomer, 5 to 10 parts of a compatibilizer, 0.5 to 1.5 parts of an antioxidant, 0.5 to 1.0 parts of a lubricant, 10 to 20 parts of a light stabilizer, 5 to 10 parts of polyphenylene ether, 5 to 10 parts of nano-calcium carbonate, 5 to 10 parts of a flame retardant and 5 to 10 parts of talc.
[0006] Preferably, the linear triblock copolymer is a hydrogenated styrene-butadiene-styrene block copolymer.
[0007] Preferably, the compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is pentaerythritol ester, the lubricant is zinc stearate, the light stabilizer is a benzotriazole light stabilizer, and the flame retardant is triphenyl phosphate.
[0008] Preferably, the linear triblock copolymer comprises the following preparation steps: Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, continuing the polymerization reaction at 50-80° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 100-200° C. and a pressure of 1-5 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segment to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
[0009] Preferably, the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer are dried in an oven at 60-80°C for 2-4 hours, the polyphenylene ether is dried at 100-120°C for 3-4 hours, the nano-calcium carbonate is dried at 100-110°C for 2-3 hours, and the talc is dried at 80-90°C for 1-2 hours.
[0010] Preferably, the average particle size of the nano calcium carbonate is 20 to 80 nm.
[0011] Preferably, the thermoplastic elastomer comprises the following preparation steps: S1, putting the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 300 to 500 rpm, and the stirring time is 5 to 10 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talc into a high-speed mixer, mixing at 110-130° C. for 8-15 minutes at a stirring speed of 400-600 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 5 to 10 minutes, and the stirring speed is 300 to 500 rpm; S4, adding the mixed materials into a twin-screw extruder, extruding and granulating at 180-220° C., the screw speed of the twin-screw extruder is 200-400 rpm, to obtain the thermoplastic elastomer.
[0012] Preferably, in S4, after extrusion granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 50 to 70° C. for 4 to 8 hours to obtain a finished thermoplastic elastomer.
[0013] Preferably, the high-speed mixer and the twin-screw extruder are both subjected to nitrogen replacement treatment before use.
[0014] The present invention provides a thermoplastic elastomer having the following beneficial effects: 1. The present invention provides basic elasticity and flexibility through linear tri-embedded copolymer, enhances toughness and wear resistance through thermoplastic polyurethane, optimizes elastic recovery and impact strength through polyolefin elastomer, and the mutual coordination of materials lays the foundation for comprehensive performance. Maleic anhydride grafted polyethylene is used as a compatibilizer to improve the compatibility of different polymers and promote uniform dispersion of fillers. The mixing of these materials enhances the tensile and impact strength of the thermoplastic elastomer.
[0015] 2. In the present invention, the polyphenylene ether is combined with the flame retardant to enhance the flame retardant effect of the flame retardant, and can maintain its own structural stability at high temperatures and form a carbon layer during combustion. Although the main function of nano calcium carbonate is to enhance the rigidity of the material, it can promote the carbonization of the material during the combustion process, improve the strength and stability of the carbon layer, and enhance the flame retardant effect of the thermoplastic elastomer. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The figure is a schematic diagram of a combined process of a thermoplastic elastomer of the present invention. DETAILED DESCRIPTION
[0017] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example: Please see attached Figure 1 The embodiment of the present invention provides a thermoplastic elastomer, comprising the following raw materials in parts by weight: 30 to 50 parts of a linear tri-block copolymer, 20 to 30 parts of a thermoplastic polyurethane, 10 to 20 parts of a polyolefin elastomer, 5 to 10 parts of a compatibilizer, 0.5 to 1.5 parts of an antioxidant, 0.5 to 1.0 parts of a lubricant, 10 to 20 parts of a light stabilizer, 5 to 10 parts of polyphenylene ether, 5 to 10 parts of nano-calcium carbonate, 5 to 10 parts of a flame retardant, and 5 to 10 parts of talc.
[0019] Linear triblock copolymers provide good elasticity and flexibility, while also possessing certain strength and heat resistance, which helps improve the comprehensive mechanical properties of the material; Thermoplastic polyurethane increases the toughness and wear resistance of the material, and improves its tear and tensile properties; Polyolefin elastomers enhance the elastic recovery performance of the material, improve low temperature resistance and impact strength; Compatible solvents promote the compatibility between different polymers, allowing each component to be evenly dispersed and improving the overall performance and stability of the material; Antioxidants prevent materials from aging and degradation due to oxidation during processing and use, thus extending the service life of the materials; Lubricants reduce friction between materials and between materials and equipment, improve processing performance, and make the product surface smoother; Light stabilizers absorb ultraviolet rays, reduce the aging effect of light on materials, and maintain the stability of the appearance and performance of materials under long-term light exposure; Polyphenylene ether, which improves the material’s heat resistance, mechanical strength and dimensional stability; Nano calcium carbonate, which enhances the rigidity and dimensional stability of the material and reduces the cost; Flame retardants, which give materials good flame retardant properties and improve the fire safety of materials; Talc improves the rigidity, heat resistance and dimensional stability of the material, while also improving the surface flatness and smoothness of the product.
[0020] Linear tri-block copolymer, thermoplastic polyurethane, polyolefin elastomer and maleic anhydride grafted polyethylene are mixed. The mutual coordination of the materials lays the foundation for comprehensive performance, and the mixing enhances the tensile and impact strength of the thermoplastic elastomer.
[0021] The linear triblock copolymer is a hydrogenated styrene-butadiene-styrene block copolymer.
[0022] The compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is pentaerythritol ester, the lubricant is zinc stearate, the light stabilizer is benzotriazole light stabilizer, and the flame retardant is triphenyl phosphate.
[0023] The linear triblock copolymer comprises the following preparation steps: Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, continuing the polymerization reaction at 50-80° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 100-200° C. and a pressure of 1-5 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segment to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
[0024] The linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer are dried in an oven at 60-80°C for 2-4 hours, the polyphenylene ether is dried at 100-120°C for 3-4 hours, the nano calcium carbonate is dried at 100-110°C for 2-3 hours, and the talc is dried at 80-90°C for 1-2 hours.
[0025] The average particle size of nano calcium carbonate is 20 to 80 nm.
[0026] Thermoplastic elastomers include the following preparation steps: S1, putting the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 300 to 500 rpm, and the stirring time is 5 to 10 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talc into a high-speed mixer, mixing at 110-130° C. for 8-15 minutes at a stirring speed of 400-600 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 5 to 10 minutes, and the stirring speed is 300 to 500 rpm; S4. Add the mixed materials into a twin-screw extruder, extrude and granulate at 180-220° C., and the screw speed of the twin-screw extruder is 200-400 rpm to obtain a thermoplastic elastomer.
[0027] In S4, after extrusion granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 50 to 70° C. for 4 to 8 hours to obtain a finished thermoplastic elastomer.
[0028] The high-speed mixer and twin-screw extruder were nitrogen purged before use.
[0029] The following is an introduction in conjunction with specific embodiments: Embodiment 1: The invention comprises the following raw materials in parts by weight: 30 parts of linear tri-embedded copolymer, 20 parts of thermoplastic polyurethane, 10 parts of polyolefin elastomer, 5 parts of compatibilizer, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of light stabilizer, 5 parts of polyphenylene ether, 5 parts of nano calcium carbonate, 5 parts of flame retardant and 5 parts of talc.
[0030] Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, and continuing the polymerization reaction at 50° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 100° C. and a pressure of 1 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segments to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
[0031] Drying of raw materials: The linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer were dried in an oven at 60°C for 2 hours, the polyphenylene ether was dried at 100°C for 3 hours, the nano-calcium carbonate was dried at 100°C for 2 hours, and the talc was dried at 80°C for 1 hour.
[0032] The average particle size of nano calcium carbonate is 20nm.
[0033] Preparation steps of thermoplastic elastomer: S1, putting the linear tri-block copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 300 rpm, and the stirring time is 5 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talcum powder into a high-speed mixer, mixing at 110° C. for 8 minutes at a stirring speed of 400 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 5 minutes, and the stirring speed is 300 rpm; S4, adding the mixed material into a twin-screw extruder, extruding and granulating at 180°C, the screw speed of the twin-screw extruder is 200 rpm. After extrusion and granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 50°C for 4 hours to obtain a finished thermoplastic elastomer.
[0034] Embodiment 2: The invention comprises the following raw materials in parts by weight: 40 parts of linear tri-embedded copolymer, 25 parts of thermoplastic polyurethane, 15 parts of polyolefin elastomer, 7.5 parts of compatibilizer, 1 part of antioxidant, 0.75 parts of lubricant, 15 parts of light stabilizer, 7.5 parts of polyphenylene ether, 7.5 parts of nano calcium carbonate, 7.5 parts of flame retardant and 7.5 parts of talc.
[0035] Preparation steps of linear triblock copolymers: Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, and continuing the polymerization reaction at 65° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 150° C. and a pressure of 3 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segments to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
[0036] Drying of raw materials: The linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer were dried in an oven at 70°C for 3 hours, polyphenylene ether was dried at 110°C for 3.5 hours, nano-calcium carbonate was dried at 105°C for 2.5 hours, and talc was dried at 85°C for 1.5 hours.
[0037] The average particle size of nano calcium carbonate is 50nm.
[0038] Preparation steps of thermoplastic elastomer: S1, putting the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 400 rpm, and the stirring time is 7.5 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talc into a high-speed mixer, mixing at 120° C. for 11.5 minutes at a stirring speed of 500 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 7.5 minutes, and the stirring speed is 400 rpm; S4, adding the mixed material into a twin-screw extruder, extruding and granulating at 200°C, the screw speed of the twin-screw extruder is 300 rpm. After extrusion and granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 60°C for 6 hours to obtain a finished thermoplastic elastomer.
[0039] Embodiment three: The invention comprises the following raw materials in parts by weight: 50 parts of linear tri-embedded copolymer, 30 parts of thermoplastic polyurethane, 20 parts of polyolefin elastomer, 10 parts of compatibilizer, 1.5 parts of antioxidant, 1 part of lubricant, 20 parts of light stabilizer, 10 parts of polyphenylene ether, 10 parts of nano calcium carbonate, 10 parts of flame retardant and 10 parts of talc.
[0040] The linear triblock copolymer is a hydrogenated styrene-butadiene-styrene block copolymer.
[0041] Preparation steps of linear triblock copolymers: Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, and continuing the polymerization reaction at 80° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 200° C. and a pressure of 5 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segments to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
[0042] Drying of raw materials: The linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer were dried in an oven at 80°C for 4 hours, polyphenylene ether was dried at 120°C for 4 hours, nano-calcium carbonate was dried at 110°C for 3 hours, and talc was dried at 90°C for 2 hours.
[0043] The average particle size of nano calcium carbonate is 80nm.
[0044] Preparation steps of thermoplastic elastomer: S1, putting the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 500 rpm, and the stirring time is 10 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talc into a high-speed mixer, mixing at 130° C. for 15 minutes at a stirring speed of 600 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 10 minutes, and the stirring speed is 500 rpm; S4, adding the mixed material into a twin-screw extruder, extruding and granulating at 220°C, the screw speed of the twin-screw extruder is 400 rpm. After extrusion and granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 70°C for 8 hours to obtain a finished thermoplastic elastomer.
[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A thermoplastic elastomer, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of a linear tri-embedded copolymer, 20-30 parts of a thermoplastic polyurethane, 10-20 parts of a polyolefin elastomer, 5-10 parts of a compatibilizer, 0.5-1.5 parts of an antioxidant, 0.5-1.0 parts of a lubricant, 10-20 parts of a light stabilizer, 5-10 parts of polyphenylene ether, 5-10 parts of nano calcium carbonate, 5-10 parts of a flame retardant and 5-10 parts of talc.
2. A thermoplastic elastomer according to claim 1, characterized in that: The linear triblock copolymer is a hydrogenated styrene-butadiene-styrene block copolymer.
3. A thermoplastic elastomer according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is pentaerythritol ester, the lubricant is zinc stearate, the light stabilizer is a benzotriazole light stabilizer, and the flame retardant is triphenyl phosphate.
4. A thermoplastic elastomer according to claim 1, characterized in that: The linear triblock copolymer comprises the following preparation steps: Under nitrogen protection, styrene monomer, initiator and cyclohexane solvent are added into the reactor; Adding butadiene monomer to the above reaction system, continuing the polymerization reaction at 50-80° C. to form a styrene-butadiene block copolymer solution; The prepared styrene-butadiene block copolymer solution is mixed with a hydrogenation catalyst, and a hydrogenation reaction is carried out at 100-200° C. and a pressure of 1-5 MPa under stirring conditions to hydrogenate and saturate the unsaturated double bonds in the butadiene chain segment to obtain a hydrogenated styrene-butadiene-styrene block copolymer; After the hydrogenation reaction is completed, the product is filtered to remove the hydrogenation catalyst, the solvent is removed by vacuum distillation, and the product is dried to obtain a pure linear triblock copolymer.
5. The thermoplastic elastomer according to claim 1, characterized in that: The linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer are dried in an oven at 60-80°C for 2-4 hours, the polyphenylene ether is dried at 100-120°C for 3-4 hours, the nano calcium carbonate is dried at 100-110°C for 2-3 hours, and the talc is dried at 80-90°C for 1-2 hours.
6. A thermoplastic elastomer according to claim 1, characterized in that: The average particle size of the nano calcium carbonate is 20 to 80 nm.
7. A thermoplastic elastomer according to claim 1, characterized in that: The thermoplastic elastomer comprises the following preparation steps: S1, putting the linear triblock copolymer, thermoplastic polyurethane and polyolefin elastomer into a high-speed mixer for high-speed stirring and mixing, and adding a compatibilizer during the stirring and mixing, the stirring speed is 300 to 500 rpm, and the stirring time is 5 to 10 minutes, to obtain A; S2, then adding antioxidant, lubricant, light stabilizer, polyphenylene ether, nano calcium carbonate, flame retardant and talc into a high-speed mixer, mixing at 110-130° C. for 8-15 minutes at a stirring speed of 400-600 rpm to obtain B; S3, further mixing the A prepared in S1 with the B prepared in S2, the mixing time is 5 to 10 minutes, and the stirring speed is 300 to 500 rpm; S4, adding the mixed materials into a twin-screw extruder, extruding and granulating at 180-220° C., the screw speed of the twin-screw extruder is 200-400 rpm, to obtain the thermoplastic elastomer.
8. A thermoplastic elastomer according to claim 7, characterized in that: In S4, after extrusion granulation, the granules are cooled by air cooling or water cooling, and the cooled material is dried in a drying oven at 50 to 70° C. for 4 to 8 hours to obtain a finished thermoplastic elastomer.
9. A thermoplastic elastomer according to claim 7, characterized in that: The high-speed mixer and the twin-screw extruder were both subjected to nitrogen replacement treatment before use.
